The Role of the United Nations Environmental Programme (UNEP) to the Development of International Environmental Law - Ijaiya, Hakeem (NIU Journal of Social Sciences, 2017)
The United Nations Environmental Programme (UNEP) is one of the prominent United Nation (UN) organs and bodies which address environmental protection issues. UNEP has been described as the environmental conscience of the UN System. UNEP has also been recognized as a major catalytic instrument for global environmental co-operation. Since its inception in 1972, UNEP has formulated scientific position, develop legal strategies and build political support to develop binding agreements (such as the Montreal Protocol, 1989, Basel Convention, 1989 etc) and nonbinding agreements. The focus of this paper is on UNEP’s birth, mandate, and contribution in the development of international environmental law. The study examines the role of UNEP as a forum for negotiations on environmental problems that fall outside the mandate of other intergovernmental organizations. The study relies on primary and secondary sources of information. The information obtained through these sources was subjected to content analysis. The study found that UNEP did not contain provisions for economic incentives to foster compliance. The study concluded that UNEP has the opportunity to include economic incentives and monitoring mechanisms in its further development of international environmental law.